The Transformation of Uzbekistan’s Juma Mosque Architecture into Avant-Garde Fashion Through Tucking and Gathering Ruffles Techniques - Dira Dwi Pramudita; Ratna Suhartini (Journal of Creative Industries and Vocational Innovation, 2026)
This study describes the application of Juma Mosque architecture in Khiva, Uzbekistan, as a source of inspiration for avant-garde fashion design through tucking and gathering ruffles techniques. The research employed a descriptive practice-based design approach using the Double Diamond model, consisting of Discover, Define, Develop, and Deliver stages. Data were collected through visual observation, design documentation, and expert judgment involving three design experts using a Guttman scale observation sheet. The data were analyzed using percentage calculations and descriptive interpretation. The results show that the tucking technique effectively represents the geometric ornamentation of the Juma Mosque through structured and consistent folds, while gathering ruffles successfully create volume and expressive visual effects but are less effective in directly representing the smooth dome silhouette. Expert assessment showed strong results in most indicators, including tucking suitability, avant-garde characteristics, volume formation, material selection, visual rhythm, balance, and conformity between the final product and the initial design. However, several aspects, such as dome silhouette representation, color suitability, and overall unity, still require further refinement. This study demonstrates that architectural forms can be translated into avant-garde fashion through fabric manipulation, producing a garment that combines conceptual inspiration, structural exploration, and visual aesthetics.